2016
DOI: 10.1038/ejcn.2016.259
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of vitamin D treatment in cystic fibrosis: a pilot randomized, controlled trial

Abstract: BACKGROUND/OBJECTIVES: Vitamin D insufficiency in cystic fibrosis is common. Vitamin D3 is currently preferred over D2. We aimed to study the efficacy of vitamin D2 and D3 at increasing serum 25-hydroxyvitamin D (s25OHD) concentrations and their effect on respiratory health in cystic fibrosis. SUBJECTS/METHODS: Sixteen CF patients were randomized to receive vitamin D2 or D3 or to serve as controls. The starting dose of 5000 IU (o 16 years old) or 7143 IU/day (⩾16 years old) was further individually adjusted. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 9 publications
5
45
1
4
Order By: Relevance
“…There were no statistically significant differences in the baseline demographics of the study groups, as reported previously . The pooled group of patients receiving D2 or D3 increased their tot‐s25OHD and free‐s25OHD concentrations at the end of intervention.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…There were no statistically significant differences in the baseline demographics of the study groups, as reported previously . The pooled group of patients receiving D2 or D3 increased their tot‐s25OHD and free‐s25OHD concentrations at the end of intervention.…”
Section: Resultssupporting
confidence: 63%
“…We speculate that D2 and D3 may both have some immunomodulatory effects, possibly affecting different pathways with different magnitude, which would speak in favour of using a combination supplement. In this pilot trial the average D2 daily dose was almost double the D3 dose, due to the lower efficacy of D2 at increasing s25OHD concentration . Local immunomodulatory effects of vitamin D in the gut are well documented , and may partially explain the difference between the effect of D2 and D3 on IgG levels.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Exocrine pancreatic insufficiency (PI), 2 CF-related diabetes (CFRD) 3 and frequent intestinal dysbiosis, as well as intestinal inflammation, may contribute to malnutrition and deficiency of fat-soluble vitamins such as vitamin D. 4 Numerous studies have examined the association between nutritional status and lung function in CF patients prior to LT, and malnutrition has been identified as a key factor for worse prognosis. 5 Vitamin D deficiency has been associated with impaired lung function in non-transplanted CF patients, 6,7 and might be associated with an increased risk of rejection and infections after LT. 8 Subsequently, nutritional support has been shown to defer impairment of pulmonary function and improve survival in LT candidates. [9][10][11][12] However, data on the impact of nutritional status on lung function in LT recipients are limited.…”
Section: Introductionmentioning
confidence: 99%